Traumatic Aneurysm on the Posterior Cerebral Artery Following Blunt Trauma in a 14-Year-Old Girl: Case Report - Zhang, C.; Chen, H.; Bai, R. (Neuropediatrics, 2011)
A 13-year-old girl sufferring from a car accident presented with a symptom of oculomotor nerve palsy. A CT scan revealed diffuse SAH in the suprasellar cistern, cisterna ambiens and interpeduncular cistern. MRI showed contusion of the left cerebral peduncle and a flowing void signal in front of the left cerebral peduncle. Cerebral angiography revealed a bilobulated aneurysm on the P1-P2 junction of the left posterior cerebral artery. Endovascular treatment was performed, with coil packing within the aneurysm and occlusion of the parent vessel. There were no neurological deficits and no recurrence of the aneurysm on follow-up studies. Endovascular embolization of traumatic posterior cerebral artery aneurysm is a safe and effective therapeutic approach.
Keywords: traumatic intracranial aneurysms; oculomotor nerve palsy; endovascular embolization